Affective temperaments (TEMPS-A) in panic disorder and healthy probands: Genetic modulation by 5-HTT variation. (25th November 2020) - Schiele, Miriam A.; Herzog, Katharina; Kollert, Leonie; Böhnlein, Joscha; Repple, Jonathan; Rosenkranz, Karoline; Leehr, Elisabeth J.; Ziegler, Christiane; Lueken, Ulrike; Dannlowski, Udo; Pauli, Paul; Arolt, Volker; et al.
Abstract: Objectives: Temperamental traits as ascertained by the Temperament Evaluation of Memphis, Pisa, Paris and San Diego Auto-Questionnaire (TEMPS-A) have been suggested as promising intermediate phenotypes of mental disorders. In anxiety disorders, however, TEMPS scales and their genetic underpinnings are still understudied. Methods: TEMPS-A scores in 109 patients with panic disorder (PD) were compared to a sample of 536 healthy probands. All participants were genotyped for serotonin transporter gene variation ( 5-HTT LPR/rs25531). Results: PD patients displayed significantly increased scores on the dysthymic, cyclothymic, irritable and anxious subscales, and lower scores on the hyperthymic subscale, respectively (all ps < 0.001) compared to healthy probands. In the total sample, the less active 5-HTT LPR/rs25531 S/LG alleles were associated with higher scores on the dysthymic, cyclothymic, irritable and anxious temperaments (all ps < 0.01), but not the hyperthymic subscale. Mediation analyses revealed anxious temperament in particular to mediate the relationship between 5-HTT genotype and PD. Conclusions: Dysthymic, cyclothymic, irritable and notably anxious temperament could serve as valuable intermediate phenotypes in efforts to unravel neurobiological, particularly serotonin system related genetic pathomechanisms associated with PD and potentially contribute to a panel of vulnerability markers guiding early targeted preventive interventions.